In vitro mutagenicity of gas-vapour phase extracts from flavoured and unflavoured heated tobacco products. (2019) - Godec, Theo Le; Crooks, Ian; Scott, Ken; Meredith, Clive
Abstract: The in vitro mutagenic and genotoxic potential of Heated Tobacco Products (HTPs) has already been studied with the particulate phase and reported previously. This study has been designed to complement the in vitro assessment of the HTP and to determine whether the inclusion of potential flavourings would alter the in vitro response by testing the other phase of the aerosol, the gas-vapour phase (GVP). Both flavoured and unflavoured Neostik GVP samples did not show any sign of mutagenic activity in the Ames test but induced a mutagenic response in the mouse lymphoma assay (MLA), however, these responses were significantly less than those of the reference cigarette, 3R4F. The results demonstrated that GVP emissions of this HTP did not induce either new qualitative or quantitative mutagenic hazards compared to 3R4F, as assessed by the Ames test (no new responsive strains) and MLA (a lower mutagenic response), respectively. A statistical comparative analysis of the responses showed that the addition of flavourings that may thermally decompose under the conditions of use did not add to the in vitro baseline responses of the unflavoured Neostik.